Sickle cell disease: A diagnosis to keep in mind (2018)
Sickle cell disease (SCD) is an autosomal recessive genetic disorder. It is the most frequent structural hemoglobinopathy worldwide, and it is produced by an alteration in the globin chain genes. In Chile, there is no data on the prevalence of SCD since it is considered a very rare condition. The incidence of this disease has been increasing due to migration of people from areas with greater presence of SCD. It is important to know and consider this diagnosis in a selected group of patients with anemia, in order to prevent and treat the different complications of this disease. This article reviews the most recent information that shows new concepts in the knowledge of the physiopathology, and especially publications of guidelines and consensus in relation to the diagnosis and management of this condition. © 2018, Sociedad Chilena de Pediatria. All rights reserved.